Effect of Collaborative Instructional Approach on Personality Traits in Geometry Achievement Among Secondary School Students in Zing Education Zone, Taraba State - Shiaki O. Bulus; Bernard A. Yukwa (Darul Yasin Al Sys, 2025)
This study investigates the effect of a collaborative instructional approach (CIA) on geometry achievement among secondary school students in Taraba State, Nigeria, with particular attention to the moderating role of personality traits. The study focused on three personality dimensions, agreeableness, conscientiousness, and openness to experience, examining how each interacts with instructional methods (CIA vs. traditional lecture) to influence academic performance. Guided by four research objectives, questions, and hypotheses, the study employed a quasi-experimental pre-test/post-test design. A total of 295 students from the Zing Education Zone participated, with grouping based on their dominant personality traits as measured by a validated inventory (Cronbach’s α = 0.95). Students received instruction in geometry using either the collaborative instructional approach or the lecture method. Descriptive statistics (mean and standard deviation) were used to address the research questions, while analysis of covariance (ANCOVA) tested the hypotheses at the 0.005 level of significance. The findings revealed that students with openness to experience achieved significantly lower scores when taught with the collaborative instructional approach compared to those taught using the lecture method, contrary to prevailing assumptions about learner-centered instruction. The study underscores the need for differentiated instructional strategies aligned with students’ personality profiles. It recommends targeted professional development programs, including seminars and workshops, for mathematics educators in the Zing Education Zone to enhance pedagogical responsiveness and subject mastery in meeting diverse learner needs.